Spousal Involvement in Collaborative Management and Glycemic Behavior Change among Patients with Diabetes Mellitus: A Systematic Review - Ika Nur Pratiwi SKep, Ns, MKep; Nursalam Nursalam MNurs (Hons); Ika Yuni Widyawati SKep, Ns, MKep, SpKepMb; Vimala Ramoo RN, MN, PhD (SAGE Publishing, 2024)
Introduction The marked increase in the number of individuals with diabetes mellitus (DM) worldwide each year has resulted in the importance of the spouse's contribution to the promotion and support of patient self-management programs. Objectives This study aimed to systematically explore the role or involvement of spouses in collaborative management and glycemic behavior change in DM. Methods Five databases including Scopus, PubMed, Cumulative Index of Nursing and Allied Health Literature, SAGE, and Web of Science were reviewed for relevant articles retrieved from 2017 to 2022. Literature search used keywords, including "Spouse," "Support," "Self-management," "Glycemic Control," and "Diabetes mellitus." The Joanna Briggs Institute guidelines were used for appraisal review of journals. The component of partner support in the self-management of patients with DM is associated with an increase in the patient's glycemic level. Results Twenty-five studies were identified that describe the different spousal roles and strategies in the promotion and support of DM management. Overall, spouses' involvement positively impacted healthy diets, higher self-efficacy, improved quality of psychological well-being, increased perceived support, and changes in glycemic-influenced behavior. Adaptation in the spouse patient relationship including maintaining cohesiveness can result in positive coping is essential in normalizing and contextualizing the chronic condition of DM. Partner-based collaboration is important for diabetes management, overcoming management barriers, and generating communal coping. Conclusion This systematic review observed that the involvement of a spouse is important in improving collaborative management and results in better glycemic behavior in patients with DM. A better understanding of the relationship between spousal involvement, coping strategies, and adherence in daily management and the subsequent use of this information are highly useful for creating targeted and effective interventions.